Understanding Euthanasia in the Light of Christ's Suffering: A Christian Ethical View on the End-of-Life Decision - Nathanael Yitshak Hadi; Andronius Wedo Yoel; Gabriel Mona (Asian Journal of Philosophy and Religion, 2026)
Euthanasia has become an increasingly relevant issue in modern society, especially as medical technology develops that allow humans to prolong or shorten life. This study aims to explore the relevance of Christ’s suffering as an ethical guide in facing end-of-life decisions, particularly related to euthanasia, from a Christian perspective. Using a qualitative approach based on textual analysis and literature review, the research examines the concept of suffering in the Bible and Christian theological writings. The main findings reveal that Christ’s suffering can serve as a model for Christians to perceive suffering as a valuable aspect of human dignity, offering an ethical alternative that rejects euthanasia as a quick solution. In conclusion, this perspective has significant implications for pastoral care, church teachings, and provides practical guidance for Christian medical professionals in supporting terminally ill patients.